2015
DOI: 10.1016/j.jphs.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene lactones derived from Saussurea lappa induce apoptosis and inhibit invasion and migration in neuroblastoma cells

Abstract: Neuroblastoma is among the most fatal of solid tumors in the pediatric age group, even when treated aggressively. Therefore, a new effective therapeutic drug(s) for neuroblastoma is urgently needed. To clarify the anticancer effects of the sesquiterpene lactones dehydrocostus lactone and costunolide, derived from Saussurea lappa, we examined the cytotoxic and migration/invasion-inhibitory effects of these compounds against neuroblastoma cell lines. Both the compounds exerted significant cytotoxicity against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Our studies are also consistent with previous studies wherein sesquiterpene lactones have been reported to exhibit anticancer activities against a range of cancer types [7]. It has also been reported that these lactones exhibit selective cytotoxic activity against cancer cells and exhibit high IC 50 values for normal cell lines indicating lower cytotoxicity for normal cells [8]. Moreover, to evaluate the effect of the solvent, we determined the cytotoxic effects of DMSO on BON-1 and the results indicated that DMSO had negligible antiproliferative effects (Figure 8).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our studies are also consistent with previous studies wherein sesquiterpene lactones have been reported to exhibit anticancer activities against a range of cancer types [7]. It has also been reported that these lactones exhibit selective cytotoxic activity against cancer cells and exhibit high IC 50 values for normal cell lines indicating lower cytotoxicity for normal cells [8]. Moreover, to evaluate the effect of the solvent, we determined the cytotoxic effects of DMSO on BON-1 and the results indicated that DMSO had negligible antiproliferative effects (Figure 8).…”
Section: Discussionsupporting
confidence: 93%
“…The results of this experiment indicated that as compared to the untreated control which did not show any signs of DNA fragmentation, dehydrocostus lactone treated cells at increasing doses indicated significant levels of DNA fragmentation. Consistent with this, several studies have reported induction of apoptosis by dehydrocostus lactone and costunolide in many types of cancer cells [7][8][9].…”
Section: Cells With Decreased λψMsupporting
confidence: 73%
“…Codonolactone also attenuated transforming growth factor-β1-mediated EMT and motility of breast cancer cells 31. Moreover, it has been reported that costunolide, derived from Saussurea lappa , induces apoptosis and inhibits cell migration and invasion in neuroblastoma cells 32. To date, only two studies have demonstrated that PT suppresses cell migration and invasion in human cancer cells.…”
Section: Discussionmentioning
confidence: 97%
“…AUX1 and PINs have been demonstrated to play important roles in polar auxin transport as an influx and efflux carriers, respectively [4,[11][12][13][44][45][46][47]. In etiolated pea seedlings, PsAUX1 and PsPIN1, PsPIN2 and PsPIN3 have been isolated [27][28][29][30][31][32][33][34][35][36][37][38][39]46,47]. Semiquantitative RT-PCR analysis revealed that DHCL substantially reduced accumulation of mRNA both of PsAUX1 and PsPIN1 in the etiolated pea seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of germacranolide-type sesquiterpene lactones with an α-methylene-γlactone derivatives obtained from natural sources have been demonstrated to exhibit pharmaceutically interesting biological activities in animals and plants. DHCL and costunolide have been demonstrated to show antitumor activity, anti-inflammatory activity, and the induction of apoptosis [26][27][28][29][30][31][32]. These compounds are also demonstrated to act as germination stimulants for the root parasitic broomrapes Orobanche cumana Wallr.…”
Section: Introductionmentioning
confidence: 99%